Selecting target market by similar measures in interval intuitionistic fuzzy set - Thao, Nguyen Xuan; Duong, Truong Thi Thuy (Technological and Economic Development of Economy, 2019)
The selection of the target market plays vital role in promoting the marketing strategies of companies. We presented is a method for target market selection. We introduce some novel similarity measures between intuitionistic fuzzy sets and the novel similarity measures between interval-valued intuitionistic fuzzy sets. They are constructed by combining exponential and other functions. Finally, we introduce a multi-criteria decision making model to select target market by using the novel similarity measure of interval intuitionistic fuzzy sets.First published online 21 June 2019